Tunnelling interlayer exchange coupling between oxide ferromagnets: Analysis for Fe3O4/vac/Fe3O4 case - SHVETS, IGOR (My University, 2009)
We have investigated tunneling interlayer exchange coupling (TIEC) between ferrimagnetic Fe3O4 ?lms via a tunneling barrier. In this investigation we employ ab-initio density functional theory to study a generic tunneling junction incorporating ferrimagnets Fe3O4/vac/Fe3O4. In contrast with previously established TIEC theory calculated here thickness dependence is non- monotonic and accompanied by TIEC sign change. Our calculations clearly demonstrate that TIEC is controlled mainly by an interfacial oxygen induced spin polarization. These results em- phasize importance of localized and strongly directional electronic interactions at the interface, thus showing limitations of free electron model treatment of the problem.
PUBLISHED
Keywords: Physics